Analisis Pengelolaan Obat di Puskesmas Sumaling Kecamatan Mare Kabupaten Bone Tahun 2022 - Hasniati Hasniati; Muh. Yusri Abadi; Suci Rahmadani (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
The management of drugs at the Sumaling Health Center experienced problems related to the demand for types of drugs that were not in accordance with the previous proposals, meanwhile there were excess types of drugs and there were also shortages of drugs. This study aims to find out information about the analysis of drug management at the Sumaling Health Center, Mare District, Bone Regency. This study uses a qualitative phenomenological approach that produces descriptive data from May-September 2022. Data collection is carried out using in-depth interviews and direct observation techniques. The informants in this study consisted of 7 people consisting of the Head of the Health Center, the Pharmacy Room Coordinator, the Pharmacy Room Staff, the Person in Charge of the Drug Distribution Section of the Health Office and 3 patients at the Sumaling Health Center. The results showed that the selection of drugs made by the Sumaling Health Center. The drug planning stage is carried out once a year. Drug procurement is carried out monthly and quarterly to the Health Office's drug warehouse, but when administering drugs at the Health Office sometimes the drugs are empty. Drugs are received monthly and then sent to the Health Office and then taken by themselves, in contrast to the quarterly Health Office which delivers them to the puskesmas. Inconvenient storage of drugs due to poor ventilation or room temperature which causes damage to drugs. The distribution of drugs at the Sumaling Health Center takes a long time to deliver drugs. The destruction and withdrawal of drugs carried out by the Sumaling Health Center is when there are expired drugs from the health service units and then collected to the puskesmas drug building then the drug management team will take them to the Health Office drug warehouse. To overcome the problem of drug management at the Sumaling Health Center, it is so that the Puskesmas will pay more attention to the applicable pharmaceutical service standards.